Teacher perception of professional skills in a project-led engineering semester - Hattum-Janssen, Natascha van (2011)
This study explores the perceptions of teachers with regard to professional skills in project-led engineering education experiences for first year engineering students at the University of Minho, Portugal. Their perception on which professional skills to include, how to develop these skills and how to assess them is studied through six semi-structured interviews with experienced teachers of the first year programme, who served as tutors as well as teachers in at least four projects. Analysis of their perceptions reveals a strong commitment to professional skills for engineering students, and also a lack of confidence in the support they can offer to help students develop these skills.